Evaluation of body composition in competitive male marathon runners - Marra, M.; Gregorio, A.; Alicante, P.; Vincenzo, O.; Sammarco, R.; Speranza, E.; Cioffi, I.; Scalfi, L. (Proceedings of the 6th International Conference on Sport Sciences Research and Technology Support - Volume 1: icSPORTS, 2018)
The marathon is a long-distance running event with an official distance of 42.195 km. Different anthropometric variables were related to endurance running performance such as weight, body fat, the sum of skin-fold thickness and circumferences of limbs. Aim of this study was to compare antropometric measurements, multifrequency (MF) BIA and phase angle between competitive marathon runners and sedentary adult individuals. Fifty-seven subjects were studied, 28 Marathon runners and 29 Control subjects. Anthropometry variables and skinfold thicknesses were determined according to standard procedure. MF BIA was performed using a multi-frequency analyzer. Biolectrical impedance index (BI index) and MF BIA ratios were calculated for the whole body. Competitive marathon runners had lower body weight and BMI compared to control subjects. There was a significant decrease of arm and forearm circumferences in the marathon runners, with no difference between groups with respect to thigh circumfere nce and calf circumference; they also exhibited lower skinfold thicknesses. Mean MF BIA ratios and phase angle were increased in the marathon group for the whole-body than control group. The use of simple methods, that are properly applied, can provide useful information for the study of body composition. In particular, the combination of anthropometry and BIA can provide a series of information that concerns both muscle mass and fat mass of the body.